Sound Creation in Khong Wong Yai Solo of Praya Sanoh Duriyang (Cham Sundaravadin) - Kaewloy, Vassakarok; Seemuang, Jatuporn; Chuppunnarat, Yootthana (Journal of Fine and Applied Arts Khon Kaen University, 2021)
This article is partial writing of a dissertation entitled ‘Splendid song selection and sound creation of Praya Sanoh Duriyang (Cham Sundaravadin)’. The purpose of this study was: to analyze crucial Khong Wong Yai solo pieces of which Praya Sanoh Duriyang had composed and have been inherited until present days namely Phaya Soke sam chan, Keakmon sam chan, Cherd Nork, and Grouw Nai sam chan. The study was a musical analyzing method particularly using Thai musical systematic approach. The paper is therefore descriptive writing to examine an idealistic construction on a Khong Wong Yai instrument of solo playing. The findings indicated that 1) the solo pieces were composed basing strictly on musical structures and principles of traditional viewpoints and perhaps occasionally using the flexibility of melodic and rhythmic contexts of song styles. 2) Arrangement of melodic equilibration on emphasizing defying-defending musical phases and special techniques. In addition, the sound creation process took up a clearness of Khong Wong Yai sound making and appropriation of physical playing between the techniques and melodic movements. This study tends to present a process of sound creation attentively focus on both melodic phrase units and entire songs. As well as, to maintain the original styles of musical tradition by schooling transmission through merely face-to-face learning methods. The process thus implicates the valuable importance of traditional practices-called oral tradition that is the dominant way of Thai music transmission in terms of preserving idealistic thought of music school in established practices.